THE HOUR TO UNDERSTAND AND FAMILIARIZE WITH CULTURAL SETTINGS FOR MARKETING IN THE THIRD MILLENNIUM - Wachinga Gikonyo Simon (Gadjah Mada International Journal of Business, 1999)
Much of the literature about culture is related to the crafting of strategic organizational culture. This is viewed as a lee-way to attainment of competitive advantage in the field of quality production at the expense of the impact that culture could have in not only influencing the consumerbehavior but more importantly in designing and planning marketing strategies in the era of globalization.This paper, therefore, undertakes to examine various cultural settings and along which their implications will be dealt with in detail in order to display the interactive relationship that prevails between culture and its attributes, and consumer behavior on one hand, and the implication of their interaction to strategize for global market opportunities by avoiding culture-marketing clash on the other hand. This paper will not provide a set of proposed strategies that should be adopted by a global marketer in order to avoid the cultural dilemmas. At best it will attempt to pin-point those areas of cultural settings that calls for intensive if not extensive understanding and familiarizing at the same note in this critical era of market competition as we head for the yet to be defined the third millennium.